Violence in schools: a holistic approach to personal transformation of at-risk youth - Meyer, Lucille (Acta criminologica, 2017)
School violence, social support, academic achievement, anti-social behaviour, youth transformation, drug and alcohol abuse, crime, gangsterism and punitive/rehabilitation measures to combat youth delinquency are frequently treated as separate domains. This article argues that a safe and effective school framework in high poverty and high crime contexts such as the Cape Flats (Western Cape) aligns the personal transformation of vulnerable learners at an individual, classroom, school and community level. Instead of fragmented interventions, a holistic approach to personal transformation of youth is advocated as a central feature to combat violence in schools located in high poverty communities. Dominant school safety approaches focus on punitive measures, emphasise physical safety and advocate for greater police involvement (as is evident in the Western Cape Education Department’s Safe Schools Programme). This article contends that a comprehensive approach, foregrounding personal transformation and addressing the social and emotional as well as the physical aspects of safety is far more valuable. This does not preclude a focus on the socio-economic contexts such as poverty and the societal inequalities, which exacerbate the violence. Personal transformation and societal reconstruction are dialectical processes that need to occur in tandem with each other.